Metabolic markers of short and long-term exogenous DL-beta-hydroxybutyrate supplementation in episodic migraine patients: an exploratory analysis of a randomized-controlled-trial - Putananickal, Niveditha; Gross, Elena C.; Orsini, Anna-Lena; Schmidt, Simone; Hafner, Patricia; Gocheva, Vanya; Nagy, Sara; Henzi, Bettina C.; Rubino, Daniela; Schädelin, Sabine; Sandor, Peter; Fischer, Dirk (Frontiers in Pharmacology, 2023)
Background: Emerging findings propose that the pathophysiology of migraine may be associated with dysfunctional metabolic mechanisms. Recent findings suggest that migraine attacks are a response to the cerebral energy deficit, and ingestion of ketone bodies stabilizes the generation of a migraine attack. Based on these findings, ketone body supplementation is postulated as a prophylactic treatment approach to restore cerebral metabolism deficiency. Metabolic markers are unexplored after exogenous ketone body supplementation in episodic migraineurs. Therefore, the present single-arm uncontrolled explorative analysis evaluated blood ketone body and glucose concentration after short and long-term 6 g exogenous DL-Mg-Ca-beta-hydroxybutyrate (DL-βHB) supplementation. Methods: The presented data are part of the MigraKet randomized-control cross-over clinical trial of 41 episodic migraineurs (Number NCT03132233). Patients were given a single dose of 6 g DL-βHB. Ketone body and glucose blood concentration were assessed before intake, 20, and 40 min after DL-βHB intake. Ketone body, glucose concentration and glycated hemoglobin values were evaluated after 12 weeks of 18 g DL-βHB ingestion (total dose), taken three times daily (6g/dose; 3x/day). Linear models explored the association between the ketone body and glucose levels. Results: Ketone body concentration increased within-group to a mean of 0.46 (0.30) mmol/L after 40 min post- DL-βHB supplementation [estimate = 0.24 mmol/L, CI = (0.20.0.27), p < 0.01]. This within-group increase of ketone body concentration did not change after repeated daily intake of DL-βHB supplementation over 12 weeks [estimate = 0.00 mmol/L, CI = (−0.03.0.04), p = 0.794]. DL-βHB intake significantly reduced blood glucose concentration within-group from a mean baseline of 4.91 (0.42) mmol/L to 4.75 (0.47) mmol/L 40 min post-DL-βHB supplementation [estimate = −0.16 mmol/L, CI = (−0.15, 0.03), p < 0.01]. Repeated DL-βHB supplementation for 12 weeks showed no change within-group in acute ketone bodies concentration [estimate = 0.00 mmol/L, CI = (−0.03.0.04), p = 0.794] and in the HbA1c value [estimate = 0.02, CI = (−0.07.0.11), p = 0.69]. Conclusion: A single dose of 6 g DL-βHB significantly elevated blood ketone bodies and decreased blood glucose concentration within-group in episodic migraineurs. Long-term DL-βHB supplementation for 12 weeks showed no effect within-group on acute ketone body concentration and had not impact on HbA1c. The elevation of the ketone body concentration was moderate, indicating that nutritional ketosis was not reached. Therefore, a dose higher than 6 g of DL-βHB is required to reach the nutritional level of ketosis. ClinicalTrials.gov Identifier: NCT03132233.